"Are You Married?": Gender and Faith in Political Ethnographic Research. (June 2021) - Thibault, Helene
In this article, I look at how political ethnography can contribute to the study of religious dynamics within conservative religious communities. Based on fieldwork conducted in Tajikistan within conservative Muslim circles, I take a reflexive stance by arguing that my informants used my status as a single foreign woman to steer interactions toward those of my religious conversion and need for marriage. Their repeated efforts and our interactions exposed the depth of their religious beliefs and its precedence over other identity markers such as ethnicity and language. This close access also allowed me to witness the exclusion and distrust that conservative Muslims face from the rest of the society as well as state authorities. Ultimately, I argue that political ethnography enables the production of a more nuanced portrait of conservative Muslims communities, which are often represented as hermetic and hostile. Political ethnography can be particularly useful to investigate sensitive issues such as religious identities and their complex relations to structures of power.